Phenylboronic acid‐functionalized F127‐oligochitosan conjugate micelles for doxorubicin encapsulation. Issue 8 (24th June 2020) - Feng, Runliang; Wang, Wanqiu; Zhu, Li; Xu, Hongmei; Chen, Shiyu; Song, Zhimei
Abstract: Doxorubicin shows good anticancer activity, but poor pharmacokinetic property and high organ toxicity restrict its clinical application. The synthesized phenylboronic acid‐modified F127‐chitosan conjugate was used to prepare doxorubicin‐loaded micelles through dialysis method. The physicochemical properties of the doxorubicin‐loaded micelles were characterized. These micelles were further evaluated for in vitro release/cytotoxicity, in vivo activity/biosafety, and pharmacokinetic studies. in vitro release experiment demonstrated that the release of doxorubicin from drug‐loaded micelles was pH‐dependent. in vitro cytotoxic study showed that the introduction of phenylboronic acid resulted in lower IC50 against B16 cells than that in non‐modified F127‐chitosan micelles group, and the doxorubicin‐loaded micelles displayed lower in vitro activity against B16, A549, and HT‐29 cells than free doxorubicin did. However, in vivo experiments confirmed that the doxorubicin‐loaded micelles were safe for mouse main organs, obviously improved pharmacokinetic parameters of doxorubicin in rat and achieved comparable inhibition of tumor growth with no animal death in B16‐bearing mice models throughout the experiment when compared with free doxorubicin. The phenylboronic acid‐sialic acid interaction and pH‐sensitive drug release might play important roles in increased tumor targeting and therapeutic effect of the doxorubicin‐loaded micelles.